Curcumin and Omega-3 Fatty Acids Enhance NK Cell-Induced Apoptosis of Pancreatic Cancer Cells but Curcumin Inhibits Interferon-γ Production: Benefits of Omega-3 with Curcumin against Cancer - Milan Fiala (Molecules, 2015)
STAT-3 and STAT-1 signaling have opposite effects in oncogenesis with STAT-3 acting as an oncogene and STAT-1 exerting anti-oncogenic activities through interferon-γ and interferon-α. The cytokine IL-6 promotes oncogenesis by stimulation of NFκB and STAT-3 signaling. Curcuminoids have bi-functional effects by blocking NFκB anti-apoptotic signaling but also blocking anti-oncogenic STAT-1 signaling and interferon-γ production. In our recent study (unpublished work [1]) in pancreatic cancer cell cultures, curcuminoids enhanced cancer cell apoptosis both directly and by potentiating natural killer (NK) cell cytotoxic function. The cytotoxic effects of curcuminoids were increased by incubation of cancer cells and NK cells in an emulsion with omega-3 fatty acids and antioxidants (Smartfish), which enhanced cancer cell apoptosis and protected NK cells against degradation. However, as also shown by others, curcuminoids blocked interferon-γ production by NK cells. The combined use of curcuminoids and omega-3 in cancer immunotherapy will require deeper understanding of their in vivo interactions with the immune system.